The rural Living Well and the collective construction of Community Life Projects - Souza, J. (Cuban Journal of Agricultural Science, 2019)
Innovation institutions are at a historic crossroads. Given the civilization crisis condi-tioning the collapse of "development", either these institutions continue reproducing "innovation for development", to the detriment of human and non-human life, or they build modes of innovation committed to the Buen Vivir (Living Well) of Peoples, an emerging paradigm alternative to the development paradigm. For institutions aspiring to contribute to the construction of rural Living Well - happy rural communities with sus-tainable livelihoods - the article provides: (a) a conceptual framework on the vulnerabil-ity-sustainability of rural livelihoods in Latin America, (b) decolonizing questions of the thinking that reproduces the development paradigm; (c) emancipatory premises to in-spire women and men wanting to build the rural Living Well in Latin America; and (d) a methodological path for the collective construction of Community Life Projects incorpo-rating 'seeds of the rural Living Well'. The conclusion is an ethical invitation to build the 'day after development'. Key words: civilization crisis, innovation for development, family farming, rural liveli-hoods, innovation for Living Well.